ANALYSING BORDERS AND SPACES: INSIGHTS FOR THE ANALYSIS OF THE TERRITORIAL CONFLICTS IN EASTERN EUROPE - Jakniūnaitė, Dovilė (Politologija, 2016)
The “frozen” territorial conflicts in Eastern Europe, which exist in the territorially divided world of sovereign states, provide the empirical context for this article in order to develop theoretical arguments. The main problem raised is the (im)possibility of the existence of the unrecognised territorial entities. The article questions how the concepts of space, territory and borders and the relationship between the territoriality and statehood in the current international relations practice and theory allow for understanding the situation in these entities. Thus, the goal is to evaluate the theoretical discussions on territoriality and borders regarding their applicability for the analysis of the “frozen” conflicts. Namely, to understand the subjectivity conditions of these entities and to comprehend how such analysis provides any new problematisations of the situation, how it gives framework to explain their strategies, behavior and the tendencies of normalisation. Three concepts (space, territory, and borders) are analysed in the article by raising three questions: a) how each of the concepts define (and constrain) the social reality and international politics; b) how such concepts are problematised; c) how such concepts help and can be used to understand the situation and possibilities of the marginal subject, which tries to overcome its own marginality, in contemporary international relations. The analysis of space demonstrates the social construction and production of space and the possibilities to find the different ways of being in the world. On the other hand, the analysis of territoriality emphasises the impossibility of the other (non-state based) subjectivity in modern international relations. This impossibility is revealed with the “traps” metaphor: they are the assumptions about the statehood and international relations. The border analysis is devoted to the analysis of the mechanisms and technologies that allow (or can allow) to move closer towards this “trap” (as looking from the perspective of the unrecognised territorial entities). The concepts are analysed from the constructivist position, treating the social facts as if they are historical. The current model of the space control divides it into closed, exclusionary, political units, defined by supposedly clear lines – borders. In this system, it is (almost) impossible to imagine any alternative ways to organise the life of the communities. This system does not imply absolute rigidity, it has breaks and inconsistencies, it is questioned and challenged. The existence of “frozen” territorial entities is also an example of some break in the system. However, the more important question is what gets treated as an ideal, as a norm, an acceptable way of organising relations. Thus, the analysis of the normalisation strategies provides a way to understanding the stability of the system. By beginning with the conceptualisations of space and territory, we allow ourselves to change the perspective in the conflict analysis and treat them not as the clash of the interests and interactions, or even identities, but as a particular space control strategy formulated through the territoriality lense. This strategy not only makes the territorially-divided world understandable and reified, but also creates the conditions for the entities which ideally should not exist. Their existence, though, is based on more or less successfully applying the sometimes repressive territorial and bordering practices. Which strategies and practices are chosen, how successful they might be and what effects they create are the tasks of the specific empirical analyses.